Mapping queer 'celebratory moment' in India: necropolitics or substantive democracy?. (21st January 2020) - Kumar, Pushpesh
Abstract: Using the theoretical framework of queer necropolitics indicating the negation of subjecthood to trans-queer of colour while assimilating white privileged gays through homonormative gestures like marriage and domesticity in the USA, the paper compares the diverse reactions of the Indian 'urban corporate gay' constituency and the marginalized transgender communities following the legalization of 'homosexuality' in India recently. Through an analysis of social media texts from the former and reflections of the latter, I propose a 'critical intersectionality' to politicize the idea of queer community mobilizations in India. While critically reflecting on the limits of 'consumer citizenship' of the privileged gay, the paper attempts to foreground the voices of transgender 'counterpublics' to draw attention to and problematize the idea of 'community' (re)iterated through popular and legal discourses.